Uruguay : Request for Stand-By Arrangement-Staff Report; Staff Supplements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uruguay. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper examines Uruguay's Request for a Stand-By Arrangement. Although the external current account shifted to a moderate deficit, mainly reflecting the recovery in imports, export performance has been robust, and gross international reserves are now about three-fourths their pre-crisis level. The authorities' program appropriately focuses on fiscal consolidation keeping inflation low through prudent monetary policy, promoting sound credit flows in a strengthened financial system, and other growth-oriented reforms. Key to maintaining macrostability will be achieving sufficiently large primary surpluses over the medium term to keep the public debt on a firm downward path.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet